2009
DOI: 10.1111/j.1365-2036.2008.03922.x
|View full text |Cite
|
Sign up to set email alerts
|

International validation of a health‐related quality of life questionnaire in patients with erosive gastro‐oesophageal reflux disease

Abstract: SUMMARY BackgroundAlthough erosive gastro-oesophageal reflux disease (GERD) is a highly prevalent condition, there is no specific, valid, reliable and sensitive questionnaire that allows evaluating treatment-induced changes in health-related quality of life (HRQoL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 28 publications
0
32
0
3
Order By: Relevance
“…To calculate the total score of the GERDyzer, the first factor is weighted by 1.0 and the second is weighted by 0.5. Holtmann et al [19] reported that they were able to obtain a consistently high Cronbach's a coefficient of 0.95, a high test-retest reliability demonstrated by an ICC of 0.91 and a responsiveness of 1.38. In Germany, Monnikes et al [20] utilized the GERDyzer to confirm the efficiency of Pantoprazole in relieving upper and lower GI symptoms in patients with erosive esophagitis.…”
Section: The Gerd Analyzer (Gerdyzer)mentioning
confidence: 95%
See 1 more Smart Citation
“…To calculate the total score of the GERDyzer, the first factor is weighted by 1.0 and the second is weighted by 0.5. Holtmann et al [19] reported that they were able to obtain a consistently high Cronbach's a coefficient of 0.95, a high test-retest reliability demonstrated by an ICC of 0.91 and a responsiveness of 1.38. In Germany, Monnikes et al [20] utilized the GERDyzer to confirm the efficiency of Pantoprazole in relieving upper and lower GI symptoms in patients with erosive esophagitis.…”
Section: The Gerd Analyzer (Gerdyzer)mentioning
confidence: 95%
“…The GERDyzer is a self-administered questionnaire primarily designed to evaluate the impact of erosive GERD on QOL and to assist medical staff in determining an optimal therapeutic strategy [19]. The GERDyzer consists of 10 dimensions that can be clustered into two factors based on factor analysis.…”
Section: The Gerd Analyzer (Gerdyzer)mentioning
confidence: 99%
“…Existing measures of HRQOL for GERD, dysphagia, achalasia, EoE, and Barrett’s esophagus were reviewed for content by three study investigators (TT, LK, and JP): Gastrointestinal Quality of Life Index (18), Quality of Life in Reflux and Dyspepsia Patients (19), GERD Analyzer (20), GERD Assessment Scales (21), Nepean Dyspepsia Index (22), MD Anderson Dysphagia Inventory (23), Laryngopharyngeal Reflux HRQOL scale (24), Reflux-QUAL (25), Eosinophilic Esophagitis QOL-A (7), Achalasia QOL (13), and the GERDQ (26). Relevant themes related to HRQOL were identified, and items from each questionnaire grouped by theme.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the GERDyzer™ is a questionnaire that evaluates the impact of GERD on a patient’s quality of life across 10 dimensions: general well-being, pain/discomfort, physical health, energy, daily activities, leisure activities, social life, diet/eating/drinking habits, mood and sleep [22]. Each dimension is assessed using a 100 mm visual analogue scale ranging from ‘not at all’ to ‘very much’, with the exception of ‘general well-being’, which is assessed from ‘excellent to ‘unbearably bad’.…”
Section: Methodsmentioning
confidence: 99%